PENGEMBANGAN PANDUAN PRAKTIKUM PERKEMBANGAN HEWAN BERBASIS PROJECT BASED LEARNING MATERI ANALISIS SPERMATOZOA - Desi Ariani Putri Br Purba; Winda Dwi Kartika; Jodion Siburian (UNIVERSITAS MUHAMMADIYAH METRO, 2022)
The practicum guide used in animal development practicum is simple and did not direct students to carry out independent of practicum. This study aims to determine the results of the development and feasibility of an animal development practicum guide based on project based learning on spermatozoa analysis material. This research is Research and development with a 4D development model with the stages of define, design, develop and disseminate. Data collection uses a material validation questionnaire, media and student responses. The results of the development at the define stage, students experienced problems in carrying out practical work on spermatozoa analysis material. At the design stage, the practicum guide is designed with a guide component adapted to the project-based learning syntax. In the develop stage, the results of material validation obtained a score of 84.35% with very good criteria, the results of media validation obtained a score of 88% with very good criteria and the results of large group trials on students obtained a score of 84.12% with very good criteria. The disseminate stage is carried out limited to the large group trial stage for the third semester of Biology Education students. It can be concluded that by using the 4D development model with the stages of define, design, develop and disseminate, the product is obtained in the form of a project-based learning-based animal development practicum guide on spermatozoa analysis material. This practical guide is suitable for use by students in the Animal Development Practicum course.Kata kunci: Panduan Praktikum, Perkembangan Hewan, Project Based Learning, Spermatozoa